Past, Present and Future: The Relationship Between Circular RNA and Immunity - Gu, Junjie; Su, Chongying; Huang, Fei; Zhao, Yuwei; Li, Jing (Frontiers in Immunology, 2022)
The immune system has evolved with us since the birth of humans. However, immune-related diseases have not yet been overcome owing to the lack of expected indicators and targeting specificity of current medical technology, which brings patients a very uncomfortable physical and mental experience along with high medical costs. Therefore, requirements for treatments with higher specificity and indicative ability are raised. Fortunately, the discovery and continuous research of circular RNAs (circRNAs) highlight a promising method among numerous methods. Although circRNAs are even regarded as metabolic wastes when discovered, as a kind of noncoding RNA (ncRNA) with a ring structure and wide distribution range in the human body, circRNAs shine brilliantly in medical research by virtue of their special nature and structure-determined functions, such as high stability, wide distribution, high detection sensitivity, and acceptable reproducibility and individual differences. Based on research on circRNAs in immunity, we systematically elaborated the hotspots of the roles of circRNAs in immune-related diseases including expression profile analysis, potential biomarker research, ncRNA axis/network construction, impacts on phenotypes, therapeutic target seeking, maintenance of nucleic acid stability and protein binding research. Besides, we summarized the current situation and problems of circRNAs in immune research, highlighted the applications and prospects of circRNAs in the treatment of immune-related diseases, and provided new insight into future directions and new strategies for laboratory research and clinical applications.